Theatrical Dining Sebagai Strategi Penguatan Identitas Budaya Bali dalam Wisata Gastronomi di Gajah Putih Restaurant Ubud - I Made Mahardika Jaya; I Made Gede Anadhi; I Gede Sedana Suci (Jayapangus Press, 2026)
Gastronomic tourism has emerged as an important strategy for preserving cultural heritage and strengthening destination branding. In Bali, this development is reflected in the implementation of theatrical dining at Gajah Putih Restaurant, which integrates culinary experiences with performing arts, cultural storytelling, and philosophical symbolism. This study aims to analyze the role of theatrical dining in strengthening Balinese cultural identity through a multisensory experience. A descriptive qualitative approach was employed using participant observation, semi-structured interviews, and literature review. The research site was purposively selected because Gajah Putih Restaurant consistently and systematically implements the theatrical dining concept. The participants consisted of ten tourists and one restaurant manager. Thematic analysis revealed that theatrical dining functions not only as a culinary innovation but also as a medium of cultural communication, in which Balinese cultural identity is represented through the philosophy of Tri Hita Karana, the symbolism of local food ingredients, ritual performances, and the active participation of tourists in co-creating meaning. This multisensory experience strengthens tourists' emotional connection with the local culture and creates a profound experiencescape. The study concludes that the integration of gastronomy and performing arts strengthens the representation of Balinese cultural identity, supports destination branding, and promotes sustainable tourism development.